Short Communication: Attempted callus induction of holoparasite Rafflesia patma Blume using primordial flower bud tissue - ADHITYO WICAKSONO; JAIME A. TEIXEIRA DA SILVA (Nusantara Bioscience, 2015)
Abstract. Wicaksono A, Teixeira da Silva JA. 2015. Attempted callus induction of holoparasite Rafflesia patma Blume using primordial flower bud tissue. Nusantara Bioscience 7: 96-101. Callus induction of a holoparasitic plant Rafflesia patma Blume was attempted using sections of a young primordial flower bud (syn. knob) of young flower tissue as the explant. The plant is an endangered species and its ex-situ conservation is very difficult. Previous attempts in the literature have not been successful, hampered by infection and explant browning. In an attempt to improve these weaknesses, in this study, following the surface disinfection of a primordial flower bud, primordial flower bud sections were cultured on Murashige and Skoog (MS) basal medium supplemented with 2 g/L activated charcoal, 1 mg/L 1-naphthaleneacetic acid and 4 mg/L N6-benzyladenine in an attempt to induce any growth. All explants browned after 2 h, and even though browning stopped after 4 days, fungal growth continued. The remaining uninfected explants that did not brown were transferred to MS medium with 1.5 mg/L kinetin in an attempt to induce callus. Two out of 6 explants browned within days but did not develop any callus. Future research needs to focus on more robust surface sterilization procedures, a wider selection of antioxidants to reduce browning, a mixed culture with the tissue of a suitable host, Tetrastigma leucostaphyllum, to stimulate organogenesis, and testing a wider range of abiotic conditions to establish an effective micropropagation protocol.